Executive summary: Italian guidelines for diagnosis, risk stratification, and care continuity of fragility fractures 2021 - Corrao, Giovanni; Biffi, Annalisa; Porcu, Gloria; Ronco, Raffaella; Adami, Giovanni; Alvaro, Rosaria; Bogini, Riccardo; Caputi, Achille Patrizio; Cianferotti, Luisella; Frediani, Bruno; Gatti, Davide; Gonnelli, Stefano; et al. (Frontiers in Endocrinology, 2023)
Background: Fragility fractures are a major public health concern owing to their worrying and growing burden and their onerous burden upon health systems. There is now a substantial body of evidence that individuals who have already suffered a fragility fracture are at a greater risk for further fractures, so suggesting the potential for secondary prevention in this field. Purpose: This guideline aims to provide evidence-based recommendations for recognizing, stratifying the risk, treating, and managing patients with fragility fracture. This is a summary version of the full Italian guideline. Methods: The Italian Fragility Fracture Team appointed by the Italian National Health Institute was employed from January 2020 to February 2021 to (i) identify previously published systematic reviews and guidelines on the field, (ii) formulate relevant clinical questions, (iii) systematically review literature and summarize evidence, (iv) draft the Evidence to Decision Framework, and (v) formulate recommendations. Results: Overall, 351 original papers were included in our systematic review to answer six clinical questions. Recommendations were categorized into issues concerning (i) frailty recognition as the cause of bone fracture, (ii) (re)fracture risk assessment, for prioritizing interventions, and (iii) treatment and management of patients experiencing fragility fractures. Six recommendations were overall developed, of which 1, 4 and 1 were of high, moderate, and low quality, respectively. Conclusions: The current guidelines provide guidance to support individualized management of patients experiencing non-traumatic bone fracture to benefit from secondary prevention of (re)fracture. Although our recommendations are based on the best available evidence, questionable quality evidence are still available for some relevant clinical questions, so future research has the potential to reduce uncertainty about the effects of intervention and the reasons for doing so at a reasonable cost.